Justificação epistêmica fundacionismo e coerentismo - Elnora Gondim (Ideas y Valores)
E. Gettier's article "Is Justified True Belief Knowledge?" changed the course of epistemology by analyzing the issue of justified truth regarding propositional knowledge and detecting a problem with the traditional definition of knowledge. The paper discusses various theories on this matter, especially those that highlight foundationalism and coherentism in its internalist aspect.